The reading achievement of Kansas urban African American fifth graders before and during No Child Left Behind - Davis, Trinity M. (Kansas State University, 2009)
With the implementation of the No Child Left Behind Act of 2001 (PL 107-110), Kansas state reading standards, benchmarks and indicators have been aligned to meet the recommendation of the National Reading Panel (2000). The components that are aligned with the Kansas reading standards are phonemic awareness, phonics, fluency, vocabulary and comprehension. High stakes testing and test scores disaggregated by race creates accountability in meeting instructional reading indicators for all students, specifically African American students. With increased pressures to meet and exceed the reading standards and close the achievement gap between Black and White students, schools are searching for instructional factors supportive of to meeting No Child Left Behind requirements. This mixed method study was conducted in three urban school districts in the state of Kansas. The quantitative study was conducted by analyzing African American fifth grade state reading assessment scores before and during implementation of No Child Left Behind to determine whether No Child Left Behind is positively impacting test scores. Data analysis revealed that African Americans increased in being at or above the standard, while decreasing the number below the standard. Out of the 180 schools in the three districts, six high performing schools were identified based on the percentage of African American students in the school, average mean scores before and during No Child Left Behind , and percentage of students at or above the standard from 2000-2007. Data were collected through detailed observational field notes and interviews with fifth grade teachers and principals in order to determine their perceptions of the instructional factors impacting reading scores. Data analysis revealed the following instructional factors impacting reading scores: analysis of data, quality professional development, teacher collaboration, high expectations, and parental involvement. Instructional reading indicators were coded throughout the observation of fifth grade classrooms. Observed indicators taught were phonics, vocabulary, comprehension of text types and text structures. This study provided perspectives of instructional strategies essential to increasing the reading strategies, skills and test scores of African American students while closing the literacy achievement gap between Black and White students in Kansas schools.
Keywords: African American reader; Reading; No Child Left Behind; Education, Reading (0535)